La mediazione penale nel diritto italiano e internazionale - Palazzo, Francesco; Bartoli, Roberto (Studi e saggi, 2011)
This book contains the proceedings of the first day of the conference Strumenti alternativi di composizione dei conflitti: la mediazione civile e penale (Alternative instruments for the settlement of disputes: civil and criminal mediation), held in Florence on 20 and 21 October 2010. In recent years criminal mediation has been the subject of acute academic reflection, beginning to open a breach in both legislation and practice. Moreover, mediation has found a consistent and real application within the international perspective. This has opened up new scenarios in which the response to offences expressing a significant illegality is broken down in line with the two paradigms of judicial and "transactional", and within which these paradigms are becoming increasingly integrated.